2011
DOI: 10.1590/s0100-40422011000700016
|View full text |Cite
|
Sign up to set email alerts
|

Uso da cromatografia gasosa bidimensional abrangente (GC×GC) na caracterização de misturas biodiesel/diesel: aplicação ao biodiesel de sebo bovino

Abstract: . The growth of biodiesel market and the implementation of regulations related to biodiesel production and biodiesel/diesel blending has encouraged the development of appropriate analytical methods to control the composition of this type of mixture. In this study, an evaluation of the potential of GC×GC for the characterization of samples of beef tallow biodiesel and the composition of blends of biodiesel/ diesel is presented. The methodology was applied to beef tallow biodiesel and its mixtures with petrodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(46 reference statements)
0
2
0
5
Order By: Relevance
“…• In another study, Moraes et al [35] showed that the technique CGxCG can show results of characterization of oils and blends of the biodiesel/petrodiesel providing the percentage of the esters in biodiesel and the diesel blends.…”
Section: Beef Tallowmentioning
confidence: 99%
“…• In another study, Moraes et al [35] showed that the technique CGxCG can show results of characterization of oils and blends of the biodiesel/petrodiesel providing the percentage of the esters in biodiesel and the diesel blends.…”
Section: Beef Tallowmentioning
confidence: 99%
“…17 In the literature, many studies have demonstrated that the GC technique can be applied to determine the content of FAME or FAEE in samples of B100 or in mixtures of diesel and biodiesel, 19 and it is also used to quantify other substances like the alcohol used in the reaction and also secondary products such as glycerol, monoacylglycerides, diacylglycerides and triacylglycerides. 1,2,[20][21][22][23][24][25][26][27] However, due to the variety of raw materials 28,29 that can be employed for biodiesel production and the importance of its production in several countries, it is strategic to develop fast 30 and economically attractive methods, through modifications such as applying different column temperatures and lengths and the use of a different internal standard 23 exhibiting similar characteristics, but not present in biodiesel composition.…”
Section: Introductionmentioning
confidence: 99%
“…Moraes [10] e colaboradores identificaram em uma amostra de bio-óleo de palha de cana-de-açúcar, ácidos, éteres, aldeídos, cetonas e fenóis por GC×GC/TOFMS utilizando o software exclusivo ChromaTOF TM . Em outro trabalho, Moraes [36] empregou a GC×GC/TOF-MS e o software ChromaTOF TM na análise qualitativa de amostras de bio-óleos de casca de arroz e caroço de pêssego, identificando 106 compostos no bio-óleo de casca de arroz e 223 compostos no bio-óleo de caroço de pêssego. Entre os compostos identificados para as duas amostras foram encontrados fenóis, ácidos, cetonas, aldeídos e éteres entre outros oxigenados.…”
Section: Introductionunclassified